STRATEGI OPTIMALISASI PENDAPATAN ASLI DAERAH (PAD): KASUS KOTA BANJARMASIN - Baban Sobandi (Jurnal Borneo Administrator, 2005)
The enactment of Law No. 33 and 34 (2004) may only achieve decentralization’s purposes if accompanied by suitable preparation from local government agencies. In this case, financial independency can be fortified by optimizing potential resources, particularly self-local revenues (pendapatan asli daerah) such as local taxes and levies. Effort to improve financial capacity, however, should also deeply consider its impacts on investment and people’s purchasing power. This paper tries to elaborate the strategy of Barjarmasin City Government in strengthening its financial capacity.